A mixed method study to explore the problems and interventions adopted among patients with Celiac disease with the view to develop and utilise the assessment tool in selected Hospitals of Maharashtra. – A Pilot Study - Mrs. Shilpa Gajendra Bakal, Dr. (Mrs) Nilima Bhore (South Eastern European Journal of Public Health, 2025)
Background: Celiac disease, a chronic autoimmune disorder triggered by gluten consumption, poses significant challenges to patients' physical, emotional, and social well-being. Effective management requires a thorough understanding of the problems faced and interventions adopted by patients. This study aims to explore these dimensions and develop a comprehensive assessment tool for use in selected hospitals of Maharashtra.